2018
DOI: 10.1007/s11284-018-1609-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemico‐mineralogical changes of ultramafic topsoil during stockpiling: implications for post‐mining restoration

Abstract: Lateritic topsoils, which are usually removed and stored apart before mining operations take place, play an essential role in the success of post‐mining restoration. They contain elements to recover chemical (organic matter, nutrients) and biological (seed and bud banks, microorganisms) fertility of the soil. Conserving topsoil fertility during storage time is essential for a successful use of topsoil during restoration. In this study, different chemico‐mineralogical properties of a lateritic topsoil from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Over the years, the issue of how to restore or rehabilitate ultramafic environments that have been affected by mining, quarrying or other activities, has gained substantial attention at the ICSEs. Three articles published in the Special Issue report on different case studies related to this topic (Boisson et al 2018;Mizuno et al 2018;Quintela Sabarı´s et al 2018).…”
Section: Nature-based Rehabilitation Of Ultramafic Disturbed Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, the issue of how to restore or rehabilitate ultramafic environments that have been affected by mining, quarrying or other activities, has gained substantial attention at the ICSEs. Three articles published in the Special Issue report on different case studies related to this topic (Boisson et al 2018;Mizuno et al 2018;Quintela Sabarı´s et al 2018).…”
Section: Nature-based Rehabilitation Of Ultramafic Disturbed Sitesmentioning
confidence: 99%
“…Quintela Sabarı´s et al (2018) report how the properties of a topsoil in a nickel-laterite opencast mining operation evolve during stripping and storage and what consequences can be expected when re-using this material in post-mining rehabilitation. The following two papers report experiences and case-studies of how the use of metallophytes can be successful for the rehabilitation of mine and quarry sites.…”
Section: Nature-based Rehabilitation Of Ultramafic Disturbed Sitesmentioning
confidence: 99%
“…With the increase of the burial depth, the losses of soil pH, total nitrogen, total phosphorus, total potassium, and organic matter are diminished. This may be because the microbial activity in the topsoil is higher than that in the soil inside the heap (Visser et al, 1984), which leads to the rapid nutrient transformation in the surface soil of the heap; and it may also be due to a small amount of rainfall in the study area in spring leading to decomposition of organic matter in topsoil and leaching of some nutrients from the soil (Quintela et al, 2018). Some studies have shown that the soil organic matter inside the heap increases after a long-term stacking of topsoil (Williamson and Johnson, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Topsoil can be used as an inoculum to provide seedbanks and microbiota to ensure the colonisation of disturbed soil (Bradshaw, 2000(Bradshaw, , 1997. However, this approach requires careful handling of topsoil, as well as stockpiling under appropriate conditions, and fast reapplication of topsoil to ensure biological activity (Echevarria and Morel, 2015;Quintela-Sabarís et al, 2018). The use of organic wastes and industrial by-products may also be considered as an amendment for soil construction (Echevarria and Morel, 2015;O'Dell and Claassen, 2009;Séré et al, 2008).…”
Section: Accepted Manuscriptmentioning
confidence: 99%